Alcohol and psychoactive substance use disorders in eating disorder patients: a controlled study - Keçeli, F.; Maner, F.; Alpkan, L.; Ergen, N.; Eradamlar, N. (Journal of Dependence, 2008)
1.485 / 5.000 Objective: This study investigated the sociodemographic characteristics, eating attitudes, alcohol and substance use disorders, family history of alcohol and other psychiatric disorders in patients diagnosed with eating disorders. Method: Sixteen female patients with anorexia nervosa and 18 female bulimia nervosa according to SCID-I diagnostic criteria who were either presenting to a private psychiatrist or currently receiving treatment were included in the study at the Neurosis Clinic of Bakırköy Mental and Nervous Diseases Training and Research Hospital, Istanbul University, and Marmara University Faculty of Medicine Psychiatry Clinics. Thirty-four healthy females served as controls. Seven of the eating disorder group consisted of anorexia nervosa patients in psychiatric wards. Diagnoses of anorexia nervosa, bulimia nervosa, and alcohol and substance use disorders were made using the SCID-I. Eating attitudes were assessed in all subjects using the Eating Attitudes Test (EAT). Results: While none of the anorexia nervosa cases had psychoactive substance use, four (22.2%) of the bulimia nervosa cases had psychoactive substance use; however, the difference was not statistically significant (p=0.11). Three of the bulimia nervosa patients using psychoactive substances had alcohol abuse (75%), and one had multiple substance abuse, including alcohol, stimulants, and cannabis. Conclusion: While no anorexia nervosa cases had a comorbid psychoactive substance use diagnosis, psychoactive substance use disorder was detected in the bulimia nervosa cases.